PENGARUH KUALITAS INFORMASI, DAYA TARIK, DAN FREKUENSI POSTINGAN TERHADAP EFEKTIVITAS KONTEN TIKTOK (STUDI KASUS KONTEN BERBAGI PADA AKUN TIKTOK @NDSHVV) - Rana Kamilah Arif, (2023)
The misalignment between content, appearance and schedule in TikTok content is often the main obstacle to the effectiveness of the content. The content and expectations of TikTok content may not match its presentation, resulting in disharmony that disrupts the overall viewer experience. Therefore, it is important to understand the factors that can make content effective on this platform. Based on this background, the problem can be formulated as the extent of the influence of information quality, attractiveness, and posting frequency on the effectiveness of content on TikTok account @ndshvv. This research aims to determine the influence of information quality, attractiveness, and posting frequency on the effectiveness of content on the TikTok platform. This research utilizes a quantitative research method with a survey approach, with purposive sampling technique, and employs the Uses and Gratification theory to understand the understanding of why and how individuals use media and how the media can satisfy individuals' needs and goals through content effectiveness with information quality, attractiveness, and posting frequency. A total of 400 respondents were obtained using the Taro Yamane formula (d = 10%) from a population of 6.5 million, which represents the followers of TikTok account @ndshvv, as the subjects of this research. Based on the results of the F hypothesis test, it is known that information quality, attractiveness, and posting frequency simultaneously influence the effectiveness of TikTok content, with a significance value of 0.000 < 0.05, indicating that there is an influence between information quality, attractiveness, and posting frequency on the effectiveness of TikTok content. Based on the results of the t hypothesis test, information quality increases content effectiveness by 0.103 units, attractiveness increases content effectiveness by 0.141 units, and posting frequency increases content effectiveness by 0.167 units. It can be concluded that posting frequency is the most influential factor on content effectiveness on the TikTok account @ndshvv.